2022
DOI: 10.1080/23802359.2022.2048212
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Trigonotis peduncularis (Boraginaceae)

Abstract: Trigonotis peduncularis (Boraginaceae) is an annual or biannual herb widely distributed in temperate Asia and East Europe. The complete chloroplast genome of T. peduncularis was sequenced by high-throughput technologies and assembled for the first time. The complete chloroplast genome of T. peduncularis was 147,508 bp in length with a GC content of 37.6%, which includes a large single-copy region (80,546 bp), a pair of inverted repeats (24,877 bp), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The C. monoica cp genome typically exists as a double-stranded circular molecule with two inverted repeats (IR) and one large single copy (LSC) [38,39]. Our assembly and annotation results show that the C. monoica cp genome length is 148,711 bp, which is in the range of other Boraginaceae species [40,41], displaying similar genome structures and gene arrangements. While the tRNA and rRNA gene compositions of the three Boraginaceae species are similar, some differences are observed in the number of PCGs.…”
Section: Discussionmentioning
confidence: 79%
“…In this research, we presented the plastomes of two taxa belonging to the Cordiaceae. The plastomes of C. monoica and C. sinensis structurally resembled the plastomes of other Boraginales species [54,55]. The plastome sizes of C. monoica and C. sinensis ranged from 151,813 bp to 152,050 bp, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 87%